Model of coorperation defense DDoS attack based on client reputation - TIAN Jun-feng; ZHU Hong-tao; SUN Dong-dong; BI Zhi-ming; LIU Qian (Tongxin xuebao)
The CDDACR（cooperation defense DDoS attack based on client reputation） model was presented to detect and defend the DDoS attack.Two detection agents made up of the CDDACR model logically:the RDA which set up on the router and the SDA which set up on the server.RDA coarse-grained detected the traffic to filter out the obvious unauthorized clients’ traffic;SDA fine-grained detected the client’s traffic to identity the cunning attack and low-flow attack from the communication.Therefore, RDA and SDA together detected the client’s network status in realtime.The experimental results show the CDDACR model can detect and defend the DDoS attack in realtime, and reduce the probability of server be attacked when the network is on the abnormity.